Identification of Fake VS Original logos using Deep Learning - et. al., Ranjith K C, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Logo or trademark conveys the significance of an organization or a product. In view of determining of the authenticity of a logo, a precise extraction of features is crucially important for any automated recognition system to succeed. Here in this proposed work, identification of fake logos are done by fusion based approach of features from SIFT and SURF which considerably does better compared to the existing methods.